THE NATURE OF HEREDITY, ENVIRONMENT, HUMAN FREEDOM, AND GOD'S HIDAYAH IN CONTEMPORARY ISLAMIC EDUCATION - Zuhriah, Zuhriah; Musthofa, Musthofa; Arifi, Ahmad (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Humans were created on this earth for a special reason, namely to be leaders (khalifah) and servants on earth, Allah gave various potentials to humans which are then expected so that humans can and are able to develop these potentials through formal and informal education. So that all the potential that is owned can be put to good use Islamic education is an education that is expected to hone every potential that an individual has. In order to get the position as expected by Allah SWT. This educational process is strongly influenced by several factors in the process of individual development, such as heredity (al-waritsah), environment (al-biah), human freedom (at-taqhayyun) and the guidance of God that students have. The purpose of this study is to see how the relationship between the elements of heredity (al-waritsah), environment (al-biah), human freedom (at-taqhayyun) and God's guidance in contemporary Islamic education. This type of research is library research, namely research that examines material objects, works and then the source of the data obtained from books, journals, and various types of reports and documents. So the elements of heredity, environment, human freedom, and God's guidance are very influential in the development of contemporary Islamic education especially in this era of globalization humans are faced with many educational and individual moral challenges, humans realize that basically, humans have the freedom to choose whatever has been given by Allah SWT, it's just that so that this freedom is not misused, the task of education is to guide, teach, and educate so that individuals are directed to the right path. With the existence of contemporary Islamic education students and educators can become a vessel in learning activities.